Effects of a futsal game on metabolic, hormonal, and muscle damage indicators of male futsal players - Bekris, E.; Gioldasis, A.; Gissis, I.; Katis, A.; Mitrousis, I.; Mylonis, E. (The Journal of Strength and Conditioning Research, 2022)
The aim of this study was to examine the effects of a futsal game on several metabolic, hormonal, and muscle damage indicators. Twenty-one male top-level futsal players participated in the study. Players were divided into 2 groups according to playing time: the long playing time (LPT) group and the short playing time (SPT) group. Game intensity parameters such as percentage of the HRmax and blood lactate concentration, as well as metabolic, hormonal, and muscle damage indicators were examined before and after a futsal game. The results showed that during the game, the intensity was up to 93% of HRmax and lactate concentrations ranged from 5.8 to 21.8 mmol/L. The LPT group showed an increased lactate dehydrogenase level compared with the SPT group (p < 0.05). Similarly, creatine kinase was significantly increased in the LPT group (p < 0.05) after the game. By contrast, nonsignificant differences were observed between groups for alanine transaminase (ALT-SGPT), aspartate transaminase (AST-SGOT), and gamma-glutamyl transferase enzymes (p > 0.05). The testosterone/cortisol ratio (T/C) reduced for both groups after the game (p < 0.05). The results of this study indicated that a futsal game have a significantly effect on several hormonal, metabolic, and muscle damage indicators for players who participate for a longer playing time in the game. Therefore, the evaluation of these volumes could assist coaches to organize specific, effective, and individualized training programs.